2013
DOI: 10.1111/jocn.12327
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects of Tai Chi exercise on people with rheumatoid arthritis

Abstract: Offering Tai Chi alongside traditional treatments for RA could promote psychological health and well-being, help inform clinical decision-making and prove cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…These findings are consistent with studies of tai chi by Waite‐Jones et al. () and Yeh et al. () where participants reported experiencing enhanced awareness and greater unity between mind and body.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with studies of tai chi by Waite‐Jones et al. () and Yeh et al. () where participants reported experiencing enhanced awareness and greater unity between mind and body.…”
Section: Discussionsupporting
confidence: 92%
“…Participants’ opinions of yoga and tai chi as “graceful,” “beautiful” and “worthwhile” meant they were appropriate and meaningful to them. Similar perceptions were noted by participants of a tai chi study who appreciated the fluid movements and likened it to that of a graceful dance (Waite‐Jones et al., ). The programme also gave the residents opportunities to carry out actions that aligned with their value.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Other interventions studied prospectively and found to impact arthritis self-efficacy and symptoms indirectly and favorably and that support a self-efficacy disease presentation link include the following: aquatic programs (Guo et al, 2009), cognitive-behavioral self-help interventions (Garnefski et al, 2013; Shigaki et al, 2013), exercise and dietary weight loss interventions (Focht et al, 2005), exercise and education interventions (Grønning et al, 2012; Hopman-Rock and Westhoff, 2000), tai-chi (Waite-Jones et al, 2013), and yoga (Evans et al, 2013) (see Table 6). …”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that exercise can reduce depression associated with pain, eventually improving quality of life (Herring, Puetz, O’Connor, & Dishman, 2012). In particular, older adults have perceived the movement-based mind-body exercise, including tai-chi (Waite-Jones, Hale, & Lee, 2013), yoga (Rogers & MacDonald, 2015), or Qi-gong (Chen, Hassett, Hou, Staller, & Lichtbroun, 2006), to be psychologically beneficial (Waite-Jones et al, 2013). One drawback the ability to participate in exercise declines with age; older adults who start exercise often drop out within 6 months, before receiving therapeutic benefits (Dishman, 1988).…”
Section: Introductionmentioning
confidence: 99%